Tri murti symbolism in candi prambanan: Revealing the cycle of creation, maintenance, and dissolution in hindu cosmology - Wika, I Made; Jha, Gautam Kumar; Seriadi, Siluh Nyoman (Life and Death: Journal of Eschatology, 2025)
Background: Prambanan Temple, as a world cultural heritage site, is a silent witness of the Tri Murti worship in Hinduism. Tri Murti, which consists of Brahma (Creator), Vishnu (Preserver), and Shiva (Redeemer), is represented by three main temples in the Prambanan Temple complex, namely Shiva Temple, Vishnu Temple, and Brahma Temple. This research aims to reveal the symbolism of Tri Murti in Prambanan Temple and its relationship with the Hindu cosmological cycle that includes creation, maintenance, and dissolution. Methods: The approach used is qualitative with analytical descriptive method, which examines the architectural structure and arrangement of the three main temples as a representation of the cycle of the universe. Findings: The results show that the arrangement and selection of the three temples illustrate the concept of Hindu cosmology related to the three stages of the life of the universe. This discovery not only confirms the spiritual significance of Prambanan Temple as a place of worship of Tri Murti but also enriches our understanding of Hindu teachings in the context of architecture and space. Conclusions: Tri Murti worship at Prambanan Temple makes an important contribution to the theory of Hindu cosmology and has significant implications for the preservation of Hindu culture and religious practices in Indonesia. Novelty/Originality of this article: This study reveals the unique connection between Tri Murti symbolism and the Hindu cosmological cycle in Prambanan's architecture, which has been rarely explored in previous research.